Globus Pallidus Internus Deep Brain Stimulation Using Frame-Based vs. Frameless Stereotaxy in Dystonia: A Single-Center Experience - Eleopra, Roberto; Rinaldo, Sara; Devigili, Grazia; Mondani, Massimo; D'Auria, Stanislao; Golfrè Andreasi, Nico; Skrap, Miran; Lettieri, Christian (Frontiers in Neurology, 2021)
Objective: Bilateral globus pallidus internus deep brain stimulation (GPi-DBS) is an established and effective therapy for primary refractory dystonia. However, the comparison of frameless vs. frame-based DBS surgery technique is still controversial. This retrospective study aims to compare the clinical outcome of two GPi-DBS surgical techniques for patients affected by primary generalized or multi-segmental dystonia. Methods: For lead's stereotaxic placement, 10 patients underwent frame-based surgery and the other 10 subjects DBS surgery with a frameless technique. Clinical features were evaluated at baseline and 6 and 12 months after surgery by means of the Burke–Fahn–Marsden Dystonia Rating Scale. Results: Frame-based GPi-DBS and frameless stereotaxic group revealed a comparable clinical outcome with no surgical complications. Conclusions: Frameless technique is safe and well-tolerated by patients and showed similar effectiveness of the frame-based stereotaxic surgery during GPi-DBS for primary dystonia. Notably, it could be a valid alternative solution because of the great advantage in improving the patient's discomfort during awake surgery.